Antimicrobial activity of red wine and oenological extracts against periodontal pathogens in a validated oral biofilm model - María C. Sánchez; Honorato Ribeiro-Vidal; Adelaida Esteban-Fernández; Begoña Bartolomé; Elena Figuero; María V. Moreno-Arribas; Mariano Sanz; David Herrera (BMC, 2019)
Abstract Background Previous research findings support an antimicrobial effect of polyphenols against a variety of pathogens, but there is no evidence of this effect against periodontal pathogens in complex biofilms. The purpose of this study was to evaluate the antimicrobial activity of red wine and oenological extracts, rich in polyphenols, against the periodontal pathogens Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum and total bacteria growing in an in vitro oral biofilm static model. Methods A previously validated biofilm model, including Streptococcus oralis, Actinomyces naeslundii, Veillonella parvula, F. nucleatum, P. gingivalis and A. actinomycetemcomitans was developed on sterile hydroxyapatite discs. Red wine (and dealcoholized wine), and two polyphenols-rich extracts (from wine and grape seeds) were applied to 72 h biofilms by dipping the discs during 1 and 5 min in the wine solutions and during 30 s and 1 min in the oenological extracts. Resulting biofilms were analyzed by confocal laser scanning microscopy and viable bacteria (colony forming units/mL) were measured by quantitative polymerase chain reaction combined with propidium monoazide. A generalized linear model was constructed to determine the effect of the tested products on the viable bacterial counts of A. actinomycetemcomitans, P. gingivalis and F. nucleatum, as well on the total number of viable bacteria. Results The results showed that red wine and dealcoholized red wine caused reduction in viability of total bacteria within the biofilm, with statistically significant reductions in the number of viable P. gingivalis after 1 min (p = 0.008) and in A. actinomycetemcomitans after 5 min of exposure (p = 0.011) with red wine. No evidence of relevant antibacterial effect was observed with the oenological extracts, with statistically significant reductions of F. nucleatum after 30 s of exposure to both oenological extracts (p = 0.001). Conclusions Although moderate, the antimicrobial impact observed in the total bacterial counts and counts of A. actinomycetemcomitans, P. gingivalis and F. nucleatum, encourage further investigations on the potential use of these natural products in the prevention and treatment of periodontal diseases.